Sports participation on multiple intelligences: a cross-sectional study of university student-athletes / Hazirah Pethie and Patricia Pawa Pitil - Pethie, Hazirah; Pitil, Patricia Pawa (2024)
Student-athletes are a unique group, facing numerous challenges in maintaining excellent academic performance while balancing their sports commitments. Participation in sports has significantly impacted their socialization, intellectual growth, and character building. It is essential to address the factors underlying these issues and devise effective strategies to help student-athletes successfully navigate their academic and athletic pursuits. Howard Gardner’s theory of multiple intelligences (MI) provides a valuable framework for understanding the diverse cognitive strengths and weaknesses of individuals. This theory posits that intelligence is not a single entity but rather a combination of several distinct intelligences, including kinesthetic, intrapersonal, logical, interpersonal, and linguistic intelligences. By evaluating student-athletes through the lens of MI, we can gain insights into how their unique intelligence profiles influence both their athletic performance and personal growth. The objective of this study was to investigate the multiple intelligences of student-athletes and examine the differences in MI subdomains based on gender, type of sport, age group, and ethnicity. To achieve this objective, a cross-sectional survey research design was employed, utilizing a sample of 182 student-athletes representing the university. Overall, the multiple intelligences of the students were high. Among the five MI subdomains, kinesthetic intelligence scored the highest (M = 21.51 ± 2.99), followed by intrapersonal (M = 20.17 ± 3.13) and logical intelligences (M = 18.78 ± 2.83). Interpersonal (M = 17.80 ± 3.11) and linguistic intelligence (M = 15.33 ± 3.35) received the lowest scores. Independent sample t-test results revealed significant differences in the kinesthetic, interpersonal, and intrapersonal intelligences between genders, while logical and interpersonal intelligences differed significantly by type of sports (p < 0.05). Logical intelligence was the only subdomain showing a significant difference between age groups, while none of the ethnicity groups showed significant differences in any of the subdomains (p > 0.05). Significant differences were found in several MI subdomains based on gender, type of sport, and age group. Specifically, kinesthetic, interpersonal, and intrapersonal intelligences differed between genders, while logical and interpersonal intelligences varied by type of sport. Additionally, logical intelligence showed differences across age groups. Overall, the results underscore the importance of a holistic approach in supporting student-athletes, leveraging their strengths in kinesthetic, intrapersonal, and logical intelligences while addressing areas like interpersonal and linguistic intelligences. Tailored strategies based on MI profiles can help balance their athletic success and personal development.